2013
DOI: 10.1002/glia.22558
|View full text |Cite
|
Sign up to set email alerts
|

Schwann cell‐derived exosomes enhance axonal regeneration in the peripheral nervous system

Abstract: Axonal regeneration in the peripheral nervous system is greatly supported by Schwann cells (SCs). After nerve injury, SCs dedifferentiate to a progenitor-like state and efficiently guide axons to their original target tissues. Contact and soluble factors participate in the crosstalk between SCs and axons during axonal regeneration. Here we show that dedifferentiated SCs secrete nano-vesicles known as exosomes which are specifically internalized by axons. Surprisingly, SC-derived exosomes markedly increase axon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
296
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 341 publications
(307 citation statements)
references
References 50 publications
(70 reference statements)
8
296
0
3
Order By: Relevance
“…In this context, Lopez-Verrilli and colleagues demonstrated that Schwann cell-derived EVs stimulated axonal growth and regeneration after nerve damage in vitro when taken up by adjacent sensory neurons (ref. 19 and Figure 2B). After internalization in damaged axons, Schwann cell-derived EVs modulated growth cone morphology and downregulated growth inhibitors, such as RhoA GTPase, both in culture and in vivo.…”
Section: R E V I E W S E R I E S : E X T R a C E L L U L A R V E S I mentioning
confidence: 88%
See 1 more Smart Citation
“…In this context, Lopez-Verrilli and colleagues demonstrated that Schwann cell-derived EVs stimulated axonal growth and regeneration after nerve damage in vitro when taken up by adjacent sensory neurons (ref. 19 and Figure 2B). After internalization in damaged axons, Schwann cell-derived EVs modulated growth cone morphology and downregulated growth inhibitors, such as RhoA GTPase, both in culture and in vivo.…”
Section: R E V I E W S E R I E S : E X T R a C E L L U L A R V E S I mentioning
confidence: 88%
“…EVs are released from virtually all cell types in the brain, including neural stem/progenitor cells (5,6), neurons (7)(8)(9), astrocytes (9-13), oligodendrocytes (13)(14)(15), and microglia (16,17) as well as Schwann cells and neurons in the peripheral nervous system (18)(19)(20). A schematic overview of potential EV-mediated interactions in the nervous system is provided in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…67 In the peripheral nervous system, Schwann cells release exosomes that are specifically internalized by axons, resulting in increased axonal regeneration after sciatic nerve injury. 68 Additionally, exosomes derived from multipotent mesenchymal stromal cells (MSCs) improve the functional recovery of neurons after stroke in a rat model. 69 Notably, our present findings demonstrate that astrocytes and fibroblasts derived from mice overexpressing PRNP exhibited higher levels of secreted exosomes, indicating a general role for PRNP in regulating exosome secretion independent of cell type.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the role of exosomes as immune-modulators and regulators of cancer progression is extensively documented (Vlassov et al, 2012). Furthermore, our recent publication indicates that Schwann cells release exosomes containing p75 and that these vesicles enhanced axonal regeneration (Lopez-Verrilli et al, 2013).…”
Section: Discussionmentioning
confidence: 99%